Cerebrovascular Disease and Statins - Beltrán Romero, Luis M.; Vallejo-Vaz, Antonio J.; Muñiz Grijalvo, Ovidio (Frontiers in Cardiovascular Medicine, 2021)
Elevated LDL-C is a causal factor for the development of atherosclerotic cardiovascular disease (ASCVD); accordingly, LDL-C lowering is associated with a decreased risk of progression of atherosclerotic plaques and development of complications. Currently, statins play a central role in any ASCVD management and prevention strategies, in relation to their lipid-lowering action and pleiotropic effects. After coronary artery disease, stroke is the most frequent cause of ASCVD mortality and the leading cause of acquired disability, a major public health problem. There is often a tendency to aggregate all types of stroke (atherothrombotic, cardioembolic, and haemorrhagic), which have, however, different causes and pathophysiology, what may lead to bias when interpreting the results of the studies. Survivors of a first atherothrombotic ischemic stroke are at high risk for coronary events, recurrent stroke, and vascular death. Although epidemiological studies show a weaker relationship between cholesterol levels and cerebrovascular disease as a whole compared with other ASCVD types, statin intervention studies have clearly demonstrated a decrease in the risk of stroke in patients with atherosclerosis of other territories and a decrease in all cardiovascular events in patients who have had a stroke. The Stroke Prevention by Aggressive Reduction in Cholesterol Levels (SPARCL) demonstrated the benefit of high doses of atorvastatin in the secondary prevention of ischemic stroke. In this review, we discuss the evidence, use and recommendations of statins in the primary and secondary prevention of stroke, and their role in other scenarios such as the acute phase of ischemic stroke, cerebral haemorrhage, cardioembolic stroke, small vessel disease, and cognitive impairment.